Narco-culturas transatlánticas: Espacios fronterizos y globalización en La reina del sur - Juan-Navarro, Santiago (Diálogos Latinoamericanos, 2018)
The article studies Arturo Perez-Reverte’s best-selling novel La reina del Sur (2002) as a paradigmatic example of the globalized trends in the promotion and distribution of narco-literature. From northwestern Mexico to southern Spain and Morocco, the novel’s is a Trans-Atlantic and Trans-Continental story of a female drug trafficker who inserts herself into larger structures of power to eventually dominate over most of her male criminal competitors. My reading focuses on Pérez-Reverte’s depiction of frontiers at multiple levels (geographical, cultural, ethnic, linguistic, literary, and sexual) within the context of two of the most pervasive examples of globalization: drug/human trafficking and migratory movements. At first sight, the novel seems to transgress these frontiers and to denounce the most abject aspects of globalization, but in the end La reina del Sur is simply a hollow tale that fails to denounce (and, in fact, embraces) neoliberal modes of circulation of capital and humans. The novel’s adaptation (2011) in one of the most successful, albeit technically deficient, narco TV series, in which moral critique is blatantly absent, only attest to the limitations of narco-novels to adopt a critical stance in the debate on criminality and globalization.